Usability Evaluation of mobile banking applications in the context of the elderly in a city of Ceará - Santos, Simone de Oliveira; Rodrigues, Agatha Bhenares Alves Martins; Ribeiro, Ítalo Mendes da Silva (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2023: Anais do XXII Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2023)
Given the increasing number of elderly people in recent years and to promote their active use of digital financial solutions, it is essential that software development is also designed considering the limitations of the elderly. The development of digital solutions requires knowledge of users’ needs and the identification of which usability criteria should be prioritized in human-computer interaction. Therefore, the problem addressed is twofold: first, to identify the primary challenges faced by the elderly when using banking applications in a small city at Ceará, and second, to gather information about their profile. In this regard, the present research aimed to evaluate the usability of banking applications in the context of the elderly and investigate the difficulties faced by this audience when using such tools. The research involved a total of 12 participants, with a pilot test included, aged between 60 and 80 years, from the city of Crateús. They were assessed through questionnaires and a usability test using the CAIXA and Banco do Brasil banking applications. The selection of these applications was due to their widespread use for social benefits, retirement, and employment-related matters. The profile of the elderly reveals that majority use smartphones for less than 4 hours per day, mainly for two primary activities: accessing social networks and making phone calls. Regarding banking technologies, nearly half of the participants have never used a banking application, and among those who have, their primary transactions involve two activities: money transfers and balance inquiries. Challenges were identified, including difficulties in identifying elements on the screen, scrolling, as well as a perceived lack of familiarity with using applications in general. As a contribution, recommendations were proposed for designing banking application interfaces based on the obtained results.